2013
DOI: 10.1167/iovs.13-11878
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film Breakup and Structure Studied by Simultaneous Video Recording of Fluorescence and Tear Film Lipid Layer Images

Abstract: Areas of tear thinning and breakup can generally be matched to corresponding regions of the TFLL as would be expected if breakup is largely due to evaporation. Surprisingly, in some examples, the corresponding lipid area was not thinner and possibly thicker than the surrounding lipid. This indicates that the lipid was a poor barrier to evaporation, perhaps because of deficiency in composition and/or structure. For example, bacterial lipases may have broken down esters into component acids and alcohols, causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 28 publications
3
100
0
Order By: Relevance
“…What is assessed in this section is the scientific evidence for the TFLL being responsible for this evaporative resistance. It is commonly believed that the TFLL forms a blanket that prevents evaporation (Lemp et al, 2007;Nichols et al, 2011;King-Smith et al, 2013b), and that a cause of dry eye syndrome is due to increased evaporation because the lipid layer is "broken". This strong belief is not supported by the evidence in the literature.…”
Section: Prevention Of Evaporationmentioning
confidence: 99%
See 2 more Smart Citations
“…What is assessed in this section is the scientific evidence for the TFLL being responsible for this evaporative resistance. It is commonly believed that the TFLL forms a blanket that prevents evaporation (Lemp et al, 2007;Nichols et al, 2011;King-Smith et al, 2013b), and that a cause of dry eye syndrome is due to increased evaporation because the lipid layer is "broken". This strong belief is not supported by the evidence in the literature.…”
Section: Prevention Of Evaporationmentioning
confidence: 99%
“…The formation of such lenses may be critical for allowing the spread of the lipid layer following a blink. Rather than a simple balling-up/ condensation of the hydrophobic molecules as suggested by the in silico modelling of Kulovesi et al (2012), King-Smith et al (2013b) provided a novel and insightful concept of a folded lipid layer to explain how the lipid layer is able to spread, and take up the possibility of how the WEs and Ch-Es might align into different domains. Although this folding model incorporates some of the features of the liquid crystal model proposed by Millar (2013) and would also resist collapse of the tear film, it has a distinct advantage in that it incorporates a mechanism for spreading the lipid layer following a blink.…”
Section: Structural Characteristics Of the Tfllmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the amount of lipid on the surface (estimated to be 0.7 to over 7 µm thick) did not affect R evap in agreement with in vivo studies (Section IV.B.1.). 22,5660 Our results indicate that when a water molecule achieves sufficient energy to escape the surface, it escapes whether the interface is a layer of lipid or air. The water molecules find their way into the lipid layer and eventually make their way to escape as a gas into the air.…”
Section: Discussionmentioning
confidence: 76%
“…36 Other studies showed that NIBUT or BUT, each of which reflects tear film stability, was not significantly correlated with LLT. 23,28,[37][38][39] In the present study, we measured both LLT and tear secretion as indicated by Schirmer's test.…”
Section: Discussionmentioning
confidence: 96%